Gender Inequality and Its Impact on Poverty Levels in Regencies and Cities in East java - Sasi Kirana Zahrani Saputri; Devanto Shasta Pratomo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
This study aims to analyze the effects of the gender development index, human development index, female labor force participation rate, and economic growth on poverty levels in regencies and cities in East Java during the 2020-2024 period. Secondary time-series data obtained from Statistics Indonesia were analyzed using panel data regression with a fixed effect model. The results show that the gender development index and the female labor force participation rate have a negative and significant effect on poverty levels, indicating that improvements in gender equality play an important role in reducing poverty. Furthermore, the human development index and economic growth do not show a significant effect. These findings indicate that poverty reduction is not determined solely by economic growth, but also by the expansion of women’s capabilities and economic participation. The results of this study emphasize the importance of gender-responsive development policies in regional poverty alleviation efforts.